Repurposing Kinase Inhibitor Bay 11-7085 to Combat Staphylococcus aureus and Candida albicans Biofilms - Escobar, Iliana E.; Possamai Rossatto, Fernanda Cristina; Kim, Soo Min; Kang, Min Hee; Kim, Wooseong; Mylonakis, Eleftherios (Frontiers in Pharmacology, 2021)
Staphylococcus aureus and Candida spp. are commonly linked with topical biofilm-associated infections such those found on chronic wounds. These biofilms are notoriously difficult to treat, highlighting the grave need to discover and study new broad-spectrum agents able to combat associated infections. We report that the kinase inhibitor Bay 11-7085 exhibits bactericidal activity against multidrug-resistant S. aureus with a minimum inhibitory concentration (MIC) of 4 µg/mL. In addition, S. aureus strain MW2 did not acquire resistance to antibiotic pressure. Furthermore, Bay 11-7085 exhibited potency against Candida albicans and the emerging pathogen Candida auris with an MIC of 0.5-1 µg/mL. Bay 11-7085 partially inhibits and eradicates biofilm formation of various pathogens, such as the VRSA (vancomycin-resistant S. aureus), as well as antifungal-resistant Candida spp. isolates. Notably, Bay 11-7085 was able to partially inhibit initial cell attachment and formation of a VRSA-C. albicans polymicrobial biofilm in vitro. In contrast to C. albicans, inhibition of VRSA biofilm was linked to initial cell attachment independent of its bactericidal activity. Finally, Bay 11-7085 was effective in vivo at increasing the lifespan of C. elegans during an S. aureus and a C. albicans infection. Our work proposes kinase inhibitor Bay 11-7085 as a potential compound capable of combating biofilms associated with the primary multidrug-resistant bacteria and yeast pathogens associated with wound infections.